Pengenalan Produksi Bersih Untuk Perbaikan Penanganan Limbah Industri Cor pada IKM Wintolo - Argaditia Mawadati; Anak Agung Putu Susastriawan; Kartinasari Ayuhikmatin Sekarjati; Andrean Emaputra; Agus Hindarto Wibowo; Ichza Nur Amami; Rio Dewangga (BADAN PENERBIT STIEPARI PRESS, 2024)
IKM Wintolo is a small home-based business engaged in the metal casting industry. In the production process, this IKM produces waste in the form of scraps of metal and metal dust which is scattered on the production floor. IKM owners still have not implemented clean production in their businesses because of the limited knowledge possessed by owners and workers. Therefore, IST AKPRIND Industrial Engineering lecturers provide guidance to the owners and workers of IKM Wintolo. From the results of this community service there has been an increase in understanding regarding clean production practices that can be carried out at IKM Wintolo. Clean production practices that can be carried out are (1) Carrying out recycling practices for scrap metal scraps from raw materials. The remains of these pieces can be collected, cleaned, and re-melted with other melted metal products to then be used again as raw materials. (2) Using coconut shells or fiber as a filter to filter used washing water which contains heavy metals. (3) Repairs to the melting furnace cover so that the metal melting process can run more optimally.